Disseminating and Using Student Assessment Information in Russia - Tyumeneva, Yulia (World Bank, Washington, DC, 2013)
This case study examines how the Russian Federation disseminates and uses information from its student assessment system, drawing lessons for other countries seeking to more effectively use their own assessment data. Russia's Unified State Examination (USE) is primarily used for student selection and certification purposes, but a variety of other uses have been attached to it, including informing pedagogy, ensuring accountability, and monitoring education quality. This variety of uses has had both positive and negative consequences for the school system. Information from international large scale assessments, for example, Program for International Student Assessment (PISA), Trends in International Mathematics and Science Study (TIMSS), and Progress in International Reading Literacy Study (PIRLS) has been widely used to introduce reforms in the school system. Factors that have affected the differential use of USE and international large scale assessment data include, among others, the purpose of a given assessment, its design features and level of credibility, and access to the assessment database. This paper is organized as follows: section one gives introduction; section two discusses the uses of student assessment information generated by the USE; section three describes the uses of international large scale assessment data to introduce educational reforms in Russia; and section four concludes with lessons regarding factors that impede or facilitate the effective use of student assessment to improve educational quality.